Pressure-sensitive adhesive articles

A pressure-sensitive adhesive composition with acrylic polymers and olefin copolymers addresses the challenge of achieving both good peel adhesion and shear resistance on polyolefin substrates by strategically incorporating the olefin copolymer, resulting in improved adhesion with reduced material usage.

JP7609852B2Active Publication Date: 2025-01-07DOW GLOBAL TECHNOLOGIES LLC +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022514670
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-16
Filing Date
2020-09-15
Publication Date
2025-01-07
Estimated Expiration
2040-09-15

AI Technical Summary

Technical Problem

Pressure-sensitive adhesives (PSAs) containing acrylic polymers face a challenge in achieving both good peel adhesion and shear resistance when bonded to polyolefin substrates, as the addition of tackifiers often compromises shear resistance.

Method used

A pressure-sensitive adhesive composition comprising one or more acrylic polymers with a glass transition temperature (Tg) of 20°C or less, combined with an olefin copolymer, where the olefin copolymer is incorporated in a specific layer to enhance peel adhesion while maintaining or reducing the overall amount used.

Benefits of technology

The composition achieves improved peel adhesion to polyolefin substrates with reduced shear resistance, demonstrating enhanced performance without excessive use of olefin copolymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609852000005
    Figure 0007609852000005
  • Figure 0007609852000006
    Figure 0007609852000006
  • Figure 0007609852000001
    Figure 0007609852000001
Patent Text Reader

Abstract

What is provided is (a) a substrate (Sa); (b) a layer (Lb) of a pressure sensitive composition (Cb) in contact with the substrate (Sa) and comprising one or more acrylic polymers (POLb) having a Tg of 20°C or less; (c) In contact with layer (Lb), (i) one or more acrylic polymers (POLc) having a Tg of 20°C or less, and (ii) a layer (Lc) comprising one or more olefin copolymers. Also provided are methods of making the pressure-sensitive adhesive articles and bonded articles made using the pressure-sensitive adhesive articles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Pressure sensitive adhesives (PSAs) containing acrylic polymers have many desirable characteristics. For example, they generally have better resistance to chemical reagents and UV light than PSAs made from many other materials. It is often desirable to provide an acrylic PSA that bonds well to polyolefin substrates. In the past, tackifier compounds have sometimes been added to PSAs to increase the peel adhesion of the PSA to the substrate. However, the addition of tackifiers usually causes an undesirable decrease in the shear resistance of the PSA.

[0002] US 2013 / 0202855 describes pressure-sensitive adhesive compositions that contain an acrylate polymer or copolymer and also contain a second polymer, which can be, for example, an ethylene-acrylic acid copolymer.

[0003] It is desirable to provide a PSA that contains an acrylic polymer and exhibits both good peel adhesion and good shear resistance when bonded to a polyolefin substrate. It is also desirable to provide a PSA that contains both an acrylic polymer and an olefin copolymer, which PSA is designed to obtain the benefits of including an olefin copolymer while reducing the use of an amount of olefin copolymer beyond that required to obtain the benefits.

[0004] The following is a description of the present invention.

[0005] The first aspect of the present invention is (a) a substrate (Sa); (b) in contact with the substrate (Sa) a layer (Lb) of a pressure-sensitive composition (Cb) comprising one or more acrylic polymers (POLb) having a Tg of 20° C. or less; (c) in contact with layer (Lb), by weight based on the weight of layer (Lc); (i) 60% to 99.5% of one or more acrylic polymers (POLc) having a Tg of 20° C. or less; and (ii) a layer (Lc) comprising 0.5% to 40% of one or more olefin copolymers.

[0006] A second aspect of the invention is a method of making a pressure-sensitive article of the first aspect, the method comprising: (A) forming a layer of an aqueous composition (Qb) containing dispersed particles of an acrylic polymer (POLb) on a first surface; (B) forming a layer of an aqueous composition (Qc) containing dispersed particles comprising (i) an acrylic polymer (POLc) and (ii) an olefin copolymer on the second surface; (C) drying the layer of the aqueous composition (Qb) to form a layer (Lb); (D) drying the layer of aqueous composition (Qc) to form a layer (Lc).

[0007] A third aspect of the invention is a bonded article made by the process of contacting a substrate (Sd) with the article of the first aspect, the substrate (Sd) being in contact with a layer (Lc). [Brief description of the drawings]

[0008] Below is a brief description of the drawings.

[0009] [Figure 1] 1 is a vertical cross-sectional view of a pressure-sensitive adhesive article of the present invention showing a substrate (Sa) (1), a layer (Lb) (2) of a composition (Cb) containing one or more acrylic polymers (POLb) having a Tg of 20° C. or less, and a layer (Lc) (3) of a composition (Cc) containing a polymer (POLc) and an olefin copolymer. FIG. 1 is not drawn to scale in any sense. For example, the horizontal dimensions of the pressure-sensitive adhesive article of the present invention shown in FIG. 1 may be 1000 times or more larger than the vertical dimensions shown in FIG. 1.

[0010] [Diagram 2]Figure 2 (also not drawn to scale) shows preferred applications to which the pressure-sensitive adhesive articles of the present invention may be applied. Figure 2 shows a layer (Lc) (3) in contact with an additional substrate (Sd) (4).

[0011] The following is a detailed description of the present invention.

[0012] As used herein, the following terms have the definitions specified, unless the context clearly indicates otherwise.

[0013] As used herein, dynamic mechanical analysis (DMA) refers to a 1 second -1 DMA refers to measurements made in the linear viscoelastic range of shear geometry at frequencies of 0.25-0.45°C. DMA measures Elastic Modulus (G'), Loss Modulus (G"), and Tan Delta (G" divided by G', synonymously referred to as "Tan (δ)"). The curve showing Tan Delta as a function of Temperature is known herein as the "Tan Delta Curve." Elastic Modulus is reported herein in units of kilopascals (kPa).

[0014] The glass transition temperature (Tg) of the material is determined by differential scanning calorimetry using the midpoint method and a temperature scan rate of 10° C. per minute according to test method ASTM D7426-08 (American Society of Testing and Materials, Conshohocken, Pa., USA).

[0015] As used herein, a "polymer" is a relatively large molecule composed of the reaction product of smaller chemical repeat units. Polymers may have structures that are linear, branched, star-shaped, looped, hyperbranched, crosslinked, or combinations thereof, and polymers may have a single type of repeat unit ("homopolymer") or they may have two or more types of repeat units ("copolymer"). Copolymers may have different types of repeat units arranged randomly, sequentially, in blocks, in other arrangements, or in any mixture or combination thereof. The size of a polymer is characterized by its weight average molecular weight, Mw, as measured by size exclusion chromatography.

[0016] As used herein, "weight of polymer" means the dry weight of the polymer.

[0017] Molecules that can react with each other to form repeat units of a polymer are known herein as "monomers." The repeat units so formed are known herein as "polymerized units" of the monomer.

[0018] Vinyl monomers have the structure [ka] wherein R 1 , R 2 , R 3 , and R 4 Each of is independently hydrogen, a halogen, an aliphatic group (such as an alkyl group), a substituted aliphatic group, an aryl group, a substituted aryl group, another substituted or unsubstituted organic group, or any combination thereof.

[0019] Some suitable vinyl monomers include, for example, styrene, substituted styrenes, dienes, ethylene, other alkenes, dienes, ethylene derivatives, and mixtures thereof. Ethylene derivatives include, for example, unsubstituted or substituted versions of the following: ethenyl esters of substituted or unsubstituted alkanoic acids (including, for example, vinyl acetate and vinyl neodecanoate), acrylonitrile, (meth)acrylic acid, (meth)acrylates, (meth)acrylamide, vinyl chloride, halogenated alkenes, and mixtures thereof. As used herein, "(meth)acrylic" means acrylic or methacrylic, "(meth)acrylate" means acrylate or methacrylate, and "(meth)acrylamide" means acrylamide or methacrylamide. "Substituted" means having at least one attached chemical group, such as, for example, an alkyl group, an alkenyl group, a vinyl group, a hydroxyl group, a carboxylic acid group, other functional groups, and combinations thereof. In some embodiments, substituted monomers include, for example, monomers with two or more carbon-carbon double bonds, monomers with hydroxyl groups, monomers with other functional groups, and monomers with combinations of functional groups. (Meth)acrylates are substituted and unsubstituted esters or amides of (meth)acrylic acid.

[0020] As used herein, an acrylic monomer is a monomer selected from (meth)acrylic acid, aliphatic esters of (meth)acrylic acid, aliphatic esters of (meth)acrylic acid having one or more substituents on the aliphatic group, (meth)acrylamide, N-substituted (meth)acrylamide, and mixtures thereof.

[0021] As used herein, a vinyl aromatic monomer is a monomer selected from styrene, alpha-alkyl styrenes, other substituted styrenes, and mixtures thereof.

[0022] As used herein, an "acrylic" polymer is one in which 50% or more of the polymerized units are acrylic monomers and 70% or more of the polymerized units are either acrylic or vinyl aromatic monomers. Percentages are by weight based on the weight of the polymer.

[0023] As used herein, an olefin polymer is a polymer in which, by weight based on the weight of the polymer, 60% by weight or more, or 70% by weight or more of the polymerized monomer units are selected from hydrocarbon alkenes, hydrocarbon dienes, and mixtures thereof. An olefin copolymer is an olefin polymer in which one or more of the polymerized units are polymerized units of one or more monomers (called "comonomers") that contain one or more oxygen atoms per molecule. An ethylene copolymer is an olefin copolymer in which 60% by weight or more, or 70% by weight or more of the polymerized units are polymerized units of ethylene, based on the weight of the polymer. A propylene copolymer is an olefin copolymer in which 70% by weight or more of the polymerized units are polymerized units of propylene, based on the weight of the polymer.

[0024] The tackifier is an organic compound having a molecular weight of 300 to 10,000 and a glass transition temperature of 0° C. or higher.

[0025] A pressure sensitive adhesive (PSA) is an adhesive that forms a bond with a substrate when pressure is applied to bring the adhesive and substrate into contact. The bond is formed without the addition of additional materials or heat. As used herein, a pressure sensitive adhesive article is an article in which a pressure sensitive adhesive is adhered to a first substrate and a surface of the PSA (the "available surface") is available for contacting a second substrate. The available surface of the PSA may or may not be in contact with a release material. The release material is a material that forms a weak bond with the PSA and can be easily removed to expose the available surface.

[0026] A composition is considered to be "aqueous" herein if it contains water in an amount of 25% by weight or greater, based on the weight of the composition.

[0027] Particles that are not spherical are considered herein to have a diameter D, and a sphere of diameter D has the same volume as a particle. Particles are said to be dispersed in a liquid medium herein if they are distributed throughout the liquid medium, and the dispersed particles may form an emulsion, latex, dispersion, slurry, or some other composition in which particles are dispersed in a liquid medium. A liquid medium is considered herein to be an aqueous medium if water forms 50% or more by weight of the liquid medium (disregarding the weight of the dispersed particles).

[0028] When an aqueous composition is said to be dried herein, it means that the composition is either dried under ambient conditions, or dried by the application of heat, exposure to a moving gas (which may or may not be heated), or a combination thereof.

[0029] The ratios presented herein are characterized as follows. For example, when a ratio is said to be 3:1 or more, it can be 3:1, or 5:1, or 100:1, but not 2:1. This characterization can be described in general terms as follows. When a ratio is said to be X:1 or more herein, it means that the ratio is Y:1, where Y is X or more. In another example, when a ratio is said to be 15:1 or less, it can be 15:1, or 10:1, or 0.1:1, but not 20:1. In general, when a ratio is said to be W:1 or less herein, it means that the ratio is Z:1, where Z is W or less.

[0030] The present invention involves the use of a substrate, which is the substrate (Sa) labeled herein. The substrate (Sa) can be any material. Paper, polymeric films and metal foils are preferred. Among the polymeric films, polyester films and olefin polymer films are preferred. Among the polymeric films, those treated at least on one side by corona discharge are preferred.

[0031] In contact with the substrate (Sa) is a layer of a composition, referred to herein as composition (Cb). Composition (Cb) contains one or more polymers, referred to herein as polymers (POLb). Polymer (POLb) has a Tg of 20° C. or less, preferably 10° C. or less. Preferably, polymer (POLb) has a Tg of −100° C. or more.

[0032] Preferably, composition (Cb) has little or no tackifier, i.e. the amount of tackifier in composition (Cb) is less than 10%, more preferably 3% or less, more preferably 1% or less, more preferably zero, by weight based on the dry weight of composition (Cb).

[0033] Preferably, the polymer (POLb) is an acrylic polymer. Preferably, the amount of polymerized units of acrylic monomers in the polymer (POLb) is 50% or more, more preferably 70% or more, more preferably 90% or more, more preferably 99% or more, by weight based on the weight of the polymer (POLb). Preferably, the polymer (POLb) has an Mw of 10,000 or more, more preferably 50,000 or more.

[0034] Preferably, the polymer (POLb) contains one or more polymerized units of n-butyl acrylate (n-BA), ethyl acrylate (EA), isooctyl acrylate (i-OA), or mixtures thereof. As used herein, "isooctyl" is an unsubstituted alkyl group containing exactly 8 carbon atoms in a branched arrangement. The term "isooctyl" includes all branched isomers of 8-carbon alkyl groups, and all mixtures of such isomers, including, for example, 2-ethylhexyl, dimethyl-hexyl, methyl-heptyl, trimethyl-pentyl, and mixtures thereof. Preferably, the total amount of polymerized units of n-BA, polymerized units of EA, and polymerized units of i-OA in the polymer (POLb) is 50% or more, more preferably 75% or more, more preferably 90% or more, by weight based on the weight of the polymer (POLb).

[0035] Preferably, every polymer in composition (Cb) having a Mw of 10,000 or greater is an acrylic polymer.

[0036] Preferably, the amount of polymer (POLb) in composition (Cb) is, by weight based on the dry weight of composition (Cb), 80% or more, more preferably 90% or more, more preferably 95% or more.

[0037] Preferably, composition (Cb) has the properties of a PSA. Preferably, composition (Cb) has an elastic modulus (G') of 20 kPa or more over a temperature range including the range of 10°C to 40°C. Preferably, composition (Cb) has an elastic modulus (G') of 1,000 kPa or less, more preferably 500 kPa or less over a temperature range including the range of 10°C to 40°C.

[0038] Preferably, the composition (Cb) is in contact with the surface of the substrate (Sa) which has been treated by corona discharge.

[0039] The layer (Lc) of the composition (Cc) is in contact with the layer (Lb) of the composition (Cb). The composition (Cc) contains one or more polymers (POLc). The necessary and preferred characteristics of the polymer (POLc) are the same as those described above for the polymer (POLb). The polymers (POLb) and (POLc) may be the same or different from each other. Preferably, the amount of (POLc) in the composition (Cc) is 70% or more, more preferably 80% or more, more preferably 85% or more, by weight based on the weight of the composition (Cc). Preferably, the amount of (POLc) in the composition (Cc) is 99.9% or less, more preferably 99.5% or less, more preferably 99% or less, more preferably 98% or less, more preferably 95% or less, more preferably 91% or less, by weight based on the weight of the composition (Cc).

[0040] Composition (Cc) additionally contains one or more olefin copolymers. Preferably, composition (Cc) contains one or more ethylene copolymers, one or more propylene copolymers, or a mixture thereof. More preferably, composition (Cc) contains one or more ethylene copolymers.

[0041] For olefin copolymers, suitable oxygen-containing comonomers include, for example, vinyl monomers with acid groups, vinyl monomers with ester groups, vinyl acetate, carbon monoxide, and mixtures thereof. Preferred comonomers are vinyl acetate, carbon monoxide, (meth)acrylic acid, substituted and unsubstituted alkyl esters of (meth)acrylic acid, maleic acid, substituted and unsubstituted alkyl monoesters and diesters of maleic acid, and mixtures thereof. More preferred comonomers are vinyl acetate, carbon monoxide, (meth)acrylic acid, glycidyl methacrylate, unsubstituted alkyl esters of (meth)acrylic acid, whose alkyl group has 4 or less carbon atoms, maleic acid, unsubstituted alkyl monoesters of maleic acid, whose alkyl group has 4 or less carbon atoms, and mixtures thereof. More preferred comonomers are (meth)acrylic acid, unsubstituted alkyl esters of (meth)acrylic acid, whose alkyl group has 2 or less carbon atoms, and maleic acid, and more preferred are vinyl acetate and acrylic acid.

[0042] Preferably, the amount of polymerized units of oxygen-containing comonomer in the olefin copolymer is 2% or more, more preferably 4% or more, more preferably 7% or more, by weight based on the weight of the olefin copolymer. Preferably, the amount of polymerized units of oxygen-containing comonomer in the olefin copolymer is 30% or less, by weight based on the weight of the olefin copolymer.

[0043] Preferably, the amount of olefin copolymer in composition (Cc) is 30% or less, more preferably 20% or less, more preferably 15% or less, by weight based on the weight of composition (Cc). Preferably, the amount of olefin copolymer in composition (Cc) is 0.1% or more, more preferably 0.5% or more, more preferably 1% or more, more preferably 2% or more, more preferably 5% or more, more preferably 9% or more, by weight based on the weight of composition (Cc).

[0044] Preferably, composition (Cc) contains little or no tackifier, i.e. preferably the amount of tackifier in composition (Cc) is less than 10%, more preferably 3% or less, more preferably 1% or less, more preferably zero, by weight based on the dry weight of composition (Cc).

[0045] It is useful to consider the amount (SUMc), defined herein as the sum of the weight of the polymer (POLc) and the weight of the olefin copolymer. Preferably, the ratio of the amount (SUMc) of the composition (Cc) to the total weight is 0.6:1 or more, more preferably 0.8:1 or more, more preferably 0.9:1 or more.

[0046] The thickness of a layer is characterized by the weight of the coat measured in grams per square meter (gsm). It is useful to characterize the total thickness (TOT), which is the sum of the thickness of layer (Lb) and the thickness of layer (Lc). Preferably, the total thickness (TOT) is 10 gsm or more, more preferably 15 gsm or more. Preferably, the total thickness (TOT) is 50 gsm or less, more preferably 45 gsm or less.

[0047] Preferably, the ratio of the thickness of the layer (Lc) to the total thickness (TOT) is 0.02:1 or more, more preferably 0.05:1 or more, more preferably 0.08:1 or more. Preferably, the ratio of the thickness of the layer (Lc) to the total thickness (TOT) is 0.8:1 or less, more preferably 0.7:1 or less, more preferably 0.6:1 or less.

[0048] The pressure-sensitive article of the present invention can be made by any method. In a preferred method, each of the layers (Lb) and (Lc) is constructed by forming a layer of an aqueous composition and then drying the layer of the aqueous composition.

[0049] Preferably, the layer (Lb) is formed by first providing an aqueous composition (AQb) containing dispersed particles of an acrylic polymer (POLb). The aqueous composition (AQb) may contain additional compounds in addition to water and the acrylic polymer (POLb). A preferred method of making the aqueous composition (AQb) is to carry out an aqueous emulsion polymerization to form dispersed particles of the aqueous polymer (POLb) in the form of a polymer latex that can function as the aqueous composition (AQb). Preferably, the dispersed polymer particles in the aqueous composition (AQb) have a volume average diameter of 50 to 750 nanometers. Preferably, the amount of the acrylic polymer (POLb) present in the aqueous composition (AQb) is 20% to 55%, by weight based on the total weight of the aqueous composition (AQb). Preferably, a layer of the aqueous composition (AQb) is applied to the surface of the substrate (Sa) and then dried to form the layer (Lb).

[0050] Similarly, a preferred method of making layer (Lc) is to provide a suitable aqueous composition (AQc), which is applied to layer (Lb) and then dried. Preferably, the aqueous composition (AQc) contains dispersed polymer particles. In some embodiments, the dispersed polymer particles contain both an acrylic polymer (POLc) and an olefin copolymer. In a preferred embodiment, the aqueous composition (AQc) contains dispersed particles of an acrylic polymer (POLc) and also contains separate dispersed particles of an olefin copolymer.

[0051] The aqueous dispersion (AQc) can be made by any method. In a preferred method, an aqueous emulsion polymerization is carried out to produce a latex of particles of an acrylic polymer (POLc) dispersed in an aqueous medium, herein labeled (AQc1). The necessary and preferred features of the aqueous composition (AQc1) are the same as those described above for the aqueous composition (AQb). Preferably, a separate aqueous composition (herein labeled (AQc2)) is provided containing particles of an olefin copolymer dispersed in an aqueous medium. Preferably, the aqueous compositions (AQc1) and (AQc2) are mixed together to form the aqueous composition (AQc). Preferably, a layer of the aqueous composition (AQc) is applied to the layer (Lb) and then dried to form the layer (Lc).

[0052] Preferably, composition (Cc) has the properties of a PSA. Preferably, composition (Cc) has an elastic modulus (G') of 20 kPa or more over a temperature range including the range of 10°C to 40°C. Preferably, composition (Cc) has an elastic modulus (G') of 1,000 kPa or less, more preferably 500 kPa or less over a temperature range including the range of 10°C to 40°C.

[0053] The pressure-sensitive article of the present invention may be made by any method. Preferably, the article is made by the following steps: (A) forming a layer of an aqueous composition (Qb) containing dispersed particles of an acrylic polymer (POLb) on a first surface; (B) forming on the second surface a layer of an aqueous composition (Qc) containing dispersed particles containing (i) an acrylic polymer (POLc) and (ii) an olefin copolymer; (C) drying the layer of aqueous composition (Qb) to form a layer (Lb); (D) drying the layer of aqueous composition (Qc) to form layer (Lc).

[0054] In some embodiments, both steps (A) and (B) are carried out, and then steps (C) and (D) are carried out simultaneously. In such an embodiment, a layer (Lb1) of the aqueous composition (Cb1) is applied to the substrate (Sa) (first surface), and while the layer (Lb1) of the aqueous composition (Cb1) is still wet, a layer (Lc1) of the aqueous composition (Cc1) is applied on top of the layer (Lb1) of the aqueous composition (Cb1) (second surface), and then the entire ensemble is dried. Among such embodiments, it is preferred that steps (A) and (B) are carried out simultaneously. That is, a multi-layer coating device is used, in which the layer (Lb1) of the aqueous composition (Cb1) is applied to the substrate (Sa) at the same time, and the layer (Lc1) of the aqueous composition (Cc1) is also applied on the layer (Lb1) of the aqueous composition (Cb1), and then the entire ensemble is dried. One suitable coating device is a slide coater. The slide coater forms a liquid composite in which a layer (Lb1) of aqueous composition (Cb1) is present beneath a layer (Lc1) of aqueous composition (Ca), the slide coater applies the entire composite layer onto the substrate (Sa) while keeping these layers intact in a manner that brings layer (Lb1) into contact with the substrate (Sa) and leaves layer (Lc1) in contact with air, and then the entire article is dried to remove water from the aqueous composition.

[0055] Also contemplated are embodiments in which the pressure-sensitive article is made by a transfer coating method, for example, a method involving making a coating layer (Cc) of the composition on a release liner (second surface), then making a coating layer of the composition (Cb) on top of a layer of the composition (first surface), then contacting the layer of the composition (Cb) with a substrate (Sa) (preferably under pressure), and then removing the release liner. In such embodiments, step (B) is performed before step (A).

[0056] It is contemplated that the pressure-sensitive adhesive article of the present invention is used by contacting it with an additional substrate (Sd). It is contemplated that pressure is applied to bring the composition (Cc) and the substrate (Sd) into intimate contact and then peel them off. It is contemplated that the result is a bonded article in which the pressure-sensitive adhesive article is still intact and the composition (Cc) is bonded to the substrate (Sd). The substrate (Sd) can be any material. Preferably, the substrate (Sd) is an olefin polymer, more preferably an olefin polymer that is not an olefin copolymer, as defined above. Preferably, the substrate (Sd) has a Tg of 50° C. or higher.

[0057] The following are examples of the present invention. Unless otherwise stated, operations were carried out at room temperature (about 23° C.). The materials used were as follows: [Table 1]

[0058] The experimental EMAA copolymer A-2050 can be prepared by standard free radical copolymerization methods using high pressure and operating in a continuous mode. The monomers are fed to the reaction mixture in a ratio related to the reactivity of the monomers and the amount desired to be incorporated. In this way, a uniform and nearly random distribution of the monomer units along the chain is achieved. Polymerization in this manner is well known and is described, for example, in U.S. Pat. No. 4,351,931 (Armitage).

[0059] Acrylic polymer emulsion polymerization was carried out as follows: A 4 liter, 5-neck reactor equipped with a condenser, mechanical stirrer, temperature controlled thermocouple, and inlets for initiator and monomer was charged with 540 g of deionized ("DI") water and heated to 87°C under a gentle nitrogen flow. In a separate vessel, a monomer emulsion was prepared by mixing 400 g of DI water, 11.9 g of DISPONIL™ FES77, 5 g of TERGITOL™ 15-S-9, 4 g of sodium carbonate, and 2024 g of a monomer mixture containing 71.5% 2-ethylhexyl acrylate ("2-EHA"), 18.5% ethyl acrylate ("EA"), 9% methyl methacrylate ("MMA"), and 1% acrylic acid ("AA"). A solution of a mixture of 1.3 g sodium carbonate and 7.5 g ammonium persulfate ("APS") in 32 g DI water was then added to the reactor. Immediately after the addition of the Na2CO3 and APS solutions, the monomer emulsion was fed into the reactor. The feeds were continued for 80 minutes. Once the monomer emulsion addition was complete, the reaction mixture was cooled to 60°C, after which a solution of tert-butyl hydroperoxide (70%) ("t-BHP") (4.7 g in 23 g DI water) and 2.8 g sodium formaldehyde bisulfite in 28 g DI water was gradually added through two separate pipes over a period of 25 minutes. Once the feeds were complete, the reaction was allowed to cool to room temperature. The resulting composition was then filtered through a 325 mesh filter cloth and diluted to 64% solids to prepare the composition for subsequent evaluation work.

[0060] The pressure sensitive adhesives were formulated as follows: All samples were lightly formulated with a wetting agent, such as SURFYNOL™ 440 wetting agent from Air Products ("440") at 0.3% (wet / wet), based on the total emulsion, to improve wet-out of laboratory drawdowns unless otherwise specified. The viscosity was then adjusted to approximately 600 mPa*s (600 cps) (Brookfield, RVDV, 30 rpm, 63#) using a thickener, such as ACRYSOL™ RM-2020 ("RM-2020") from The Dow Chemical Company, Midland, Michigan, and the final pH was adjusted to 7.0-7.5 using ammonia.

[0061] The PSA emulsion was blended with ethylene copolymer dispersion (eg, COHESA™ 3050, ELVAX™ 220W dispersion, etc.) according to the dosage levels in the table below (wet weight based on total weight of emulsion) with proper agitation.

[0062] Laboratory Drawdown Polypropylene ("PP") film (60 micrometers thick) was pretreated by corona treatment prior to lamination. The formulated adhesive was coated onto release paper and dried at 80°C for 5 minutes. The PP film was laminated with a release liner coated with a pressure sensitive adhesive.

[0063] The adhesive laminates were conditioned in a controlled environment (22.2-23.3°C (72-74°F) and 50% relative humidity) for at least one day before performance testing.

[0064] Peel strength test: Peel strength test at 90° on a high density polyethylene (HDPE) test plate was performed according to FINAT test method No. 1. FINAT is the European Association for the Self-Adhesive Label Industry (Laan van Nieuw-Oost Indie 131-G, 2593 BM The Hague, PO Box 85612, 2508 CH The Hague, The Netherlands). Prior to testing, sample strips were applied to the test plate with a dwell time of 20 minutes. All samples failed as an "adhesive" failure mode.

[0065] The results are shown in the table below. "C" stands for comparative and "I" stands for invention. "Acrylic" refers to the acrylic polymer described above. The numbers in parentheses refer to the parts based on the wet weight of the acrylic polymer latex. "ECP1" refers to COHESA™ 3050H (38.5-41.4% active solids) as above. Numbers in parentheses refer to parts based on wet weight of ECP1 aqueous dispersion. "ECP2" refers to the ELVAX™ 220W dispersion at 40% solids as above. Numbers in parentheses refer to parts based on wet weight of ECP2 aqueous dispersion. "ECP3" refers to the A-20505 dispersion at 20% solids as above. Numbers in parentheses refer to parts based on wet weight of ECP3 aqueous dispersion. "Thickness" is the combined thickness of Layer 1 and Layer 2 in gsm (grams of dry composition per square meter). "ECP Layer" is the ratio of the dry weight of the layer containing ECP divided by the combined dry weight of Layers 1 and 2 multiplied by 100 (ie, expressed as a percentage). "ECP%" is the dry weight of ECP polymer divided by the sum of the dry weight of layer 1 and the dry weight of layer 2 multiplied by 100 (ie, expressed as a percentage). "Peel" is the result of the 90 degree peel test described above in Newtons (for a sample having a width of 1 inch). [Table 2]

[0066] Comparison of C-1 and I-1: In Example I-1, layer 2 has the same composition as the entire composition of C1 (i.e., 1 part ECP), but in Example I-1, the ECP is placed only in layer 2, which has the same mass as layer 1. Thus, overall, Example I-1 uses half the amount of ECP used in C-1, and Example I-1 concentrates its ECP in layer 2, which is in contact with the HDPE test panel. I-1 has better peel strength than C-1. This demonstrates that placing the ECP in the top layer results in a pressure-sensitive article with improved peel adhesion to HDPE while using less ECP component. It is desirable to obtain improved peel adhesion without using unnecessarily large amounts of ECP.

[0067] Comparison of C-2 and I-2: Example I-2 has a layer 2 with a higher concentration of ECP, but the thickness of layer 2 is relatively thin. Thus, I-2 and C-2 have about the same total amount of ECP. However, I-2 has a much higher peel strength with HDPE, indicating that placing the ECP in the top layer improves performance.

[0068] Comparison of C-3 vs. I-3: This comparison is similar to the comparison above for C-1 vs. I-1. That is, I-3 uses half the amount of ECP compared to C-3, but I-3 places its ECP in the top layer, improving peel adhesion to HDPE. This comparison still applies to the lower overall levels of ECP in I-1 and the higher overall levels of ECP in I-3. [Table 3]

[0069] Comparison of C-4 and I-4: Same as comparison of C-3 and I-3, but using a different olefin copolymer. That is, even with a different olefin copolymer, higher peel adhesion to HDPE could be achieved with half the amount of olefin copolymer when the olefin copolymer was placed on the top layer.

[0070] Comparison of C-5 and I-5: Same as comparison of C-3 and I-3, but using another different olefin copolymer, i.e., a third olefin copolymer was used, but higher peel adhesion to HDPE was achieved with half the amount of olefin copolymer when the olefin copolymer was placed in the top layer.

Claims

1. 1. A pressure sensitive adhesive article comprising: (a) a substrate (Sa); (b) in contact with said substrate (Sa), a layer (Lb) of a pressure sensitive composition (Cb) comprising one or more acrylic polymers (POLb) comprising ethyl acrylate and 2-ethylhexyl acrylate; (c) in contact with said layer (Lb), in a weight based on the weight of layer (Lc), (i) 60% to 99.5% of one or more acrylic polymers (POLc) comprising ethyl acrylate and 2-ethylhexyl acrylate, said acrylic polymer having 50% or more by weight of polymerized units that are acrylate monomers, based on the weight of the polymer; and (ii) a layer (Lc) comprising 0.5% to 40% of one or more olefin copolymers, said olefin copolymer being an ethylene copolymer containing polymerized units of vinyl acetate or acrylic acid, or a mixture thereof, said ethylene copolymer having 60% or more by weight of polymerized units, based on the weight of the polymer, being polymerized units of ethylene.

2. A method of making the pressure-sensitive article of claim 1, comprising: (A) forming a layer of an aqueous composition (Qb) containing dispersed particles of the acrylic polymer (POLb) on a first surface; (B) forming on the second surface a layer of an aqueous composition (Qc) containing (i) said acrylic polymer (POLc) and (ii) dispersed particles containing said olefin copolymer; (C) drying the layer of the aqueous composition (Qb) to form the layer (Lb); (D) drying said layer of said aqueous composition (Qc) to form said layer (Lc).

3. 3. The method of claim 2, wherein the aqueous composition (Qb) is made by a process comprising aqueous emulsion polymerization of one or more monomers to produce dispersed particles of said acrylic polymer (POLb).

4. A bonded article made by the process of contacting a substrate (Sd) with the article of claim 1, wherein the substrate (Sd) is in contact with the layer (Lc).

5. The bonded article of claim 4, wherein the substrate (Sd) is a polyolefin.

Citation Information

Patent Citations

  • Aqueous adhesive for hardly adherable substrate and for low temperature

    JP2006137949A

  • Olefin block copolymer pressure-sensitive adhesive

    JP2015507040A

  • multilayer pressure sensitive adhesive

    JP2016514184A

  • Multi-layer pressure-sensitive adhesive

    JP2016516838A

  • Water-based pressure-sensitive adhesive composition and method of making same

    JP2020510735A